Ativismo Judicial e Direitos Humanos: exercício da jurisdição constitucional e efetividade dos direitos - Santos, Bruno Calife dos (2015)
The growing range of stabling Human Rights, since appear to be contemporary demand inseparable to the evolution of democratic societies, prevents the state to take a shy profile and involves the assumption of responsibilities by the powers that be, including the judiciary itself, despite its character essentially inert. Faced thus a certain passivity of the legislative and executive branches for the development of instruments of defense and protection of these prerogatives and on the structuring of public policy and regulatory guarantees aimed at its implementation, it is conjectured about the causes and consequences of expanding the profile of judicial activity in order to examine whether the rapprochement between the judicial creation of law and human rights, brokered by the exercise of constitutional jurisdiction, if electing, as the central figure of this action the Supreme Court. Thus, it remains to ask to what extent the expansion of the profile of this type of jurisdiction and its respective haughtiness leads to greater effectiveness of the Human Rights circumstances imagined by the use of a hermeneutic result of principled openness and ontological relationship between them and the fundamental rights protectable by the state. The analysis is guided by the literature review and critical perspective, both brought together by a descriptivist posture.